Комунікативні інструменти підтримки процесів сталого розвитку у впровадженні економічних реформ - Berezovska, N. I. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
Theses are intended to study the question of whether the ecosystem approach promotes the involvement of a wide range of stakeholders, can complicate decision-making due to conflicts of interest and power dynamics. Less influential parties, such as local communities, risk being marginalized, which can undermine the goals of sustainable development. Effective public administration can optimize the allocation of resources and support reforms, but bureaucratic inefficiency often becomes a barrier. Digitalization offers tools for improving communication and public engagement, but can increase inequality due to limited access to technology. The balance between innovation and inclusion remains key for sustainable development.